The Spear: An Effective Weapon Since Antiquity (Revista de Artes Marciales Asiáticas, 2012)
The spear is perhaps man’s oldest weapon, and may even be his oldest tool. Over the hundreds of thousands of years of the weapon’s existence, it evolved from a pointed stick into an efficient hunting missile, and then became the most effective hand-held bladed weapon humans ever devised. The spear and its use is the only martial art originally devised for use against species other than our own, and more than any other weapon, the spear emphasizes the relationship between hunting and warfare. Virtually without exception, the spear is present wherever there are humans. The spear may claim to be the senior martial art, and the weapon is still in use today. Early techniques are preserved by the small number of Japanese sojutsu schools, and modern Chinese martial artists have developed elegant and impressive gymnastic routines for the spear. The javelin throw is a modern Olympic track and field event, and there are people who have resurrected the Aztec atlatl for sporting competition. Today, the spear is still used in Europe for hunting wild boar, and the continued issue of the obsolete bayonet to modern soldiers testifies to a deep, almost instinctive respect still possessed by the military for the spear.